2023
DOI: 10.3390/antibiotics12091431
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Improve Energy Efficiency during Antimicrobial Blue Light Inactivation: Application of Pulse-Width Modulation Dimming to Balance Irradiance and Irradiation Time

Wanqing Zhang,
Ping Su,
Jianshe Ma
et al.

Abstract: Antimicrobial blue light (aBL) is an effective non-destructive inactivation technique and has received increasing attention. Despite its significance, the existing research has not thoroughly delved into the impacts of irradiance and irradiation time on enhancing energy efficiency during aBL inactivation and the explanation of the enhancement effect of pulse exposure. In this paper, a series of Escherichia coli inactivation experiments with different duty cycles, pulse frequencies, and irradiation times were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(82 reference statements)
1
0
0
Order By: Relevance
“…5 and 7 demonstrate that the enhancement in inactivation efficacy observed for lower irradiance exposures is apparent for various S. aureus and P. aeruginosa populations in suspension. These findings support those of Zhang et al ( 2023 ), who, whilst investigating the energy efficiency of pulsed 405-nm light for inactivation of E. coli suspensions, demonstrated that exposure time has greater influence over inactivation than that of irradiance, thus suggesting that greater reductions could be achieved when lower irradiances are employed over extended time periods, compared to higher irradiances over shorter time periods. By contrast, however, results for S. aureus exposed at an initial population density of 10 9 CFUmL −1 deviate from the overall findings of this study for reasons that are not yet fully understood.…”
Section: Discussionsupporting
confidence: 89%
“…5 and 7 demonstrate that the enhancement in inactivation efficacy observed for lower irradiance exposures is apparent for various S. aureus and P. aeruginosa populations in suspension. These findings support those of Zhang et al ( 2023 ), who, whilst investigating the energy efficiency of pulsed 405-nm light for inactivation of E. coli suspensions, demonstrated that exposure time has greater influence over inactivation than that of irradiance, thus suggesting that greater reductions could be achieved when lower irradiances are employed over extended time periods, compared to higher irradiances over shorter time periods. By contrast, however, results for S. aureus exposed at an initial population density of 10 9 CFUmL −1 deviate from the overall findings of this study for reasons that are not yet fully understood.…”
Section: Discussionsupporting
confidence: 89%